“It's Just Presence,” the Contributions of Aboriginal and Torres Strait Islander Health Professionals in Cancer Care in Queensland - de Witt, Audra; Cunningham, Frances C.; Bailie, Ross; Percival, Nikki; Adams, Jon; Valery, Patricia C. (Frontiers in Public Health, 2018)
Objectives: The aim of this research was to explore health professionals’ perspectives of the provision of follow-up cancer care for Aboriginal and Torres Strait Island patients in Queensland. Methods: Semi-structured interviews were conducted with Indigenous and non-Indigenous health professionals who had experience providing care for Indigenous cancer patients in the primary health care and hospital setting. Results: Participants were recruited from six Aboriginal Community Controlled Health Services (n=17) and from a tertiary hospital (n=9) across urban, regional and remote geographical settings. Culturally safe care, psychological support, determining patient needs, practical assistance, and advocating for Indigenous health were identified as enablers to support the needs of Indigenous patients when accessing cancer care, and Indigenous health professionals were identified as the key enabler. Conclusion: Indigenous health professionals significantly contribute to the provision of culturally competent follow-up cancer care by increasing the accessibility of follow-up cancer care services and by supporting the needs of Indigenous cancer patients. All health professionals need to work together and be sufficiently skilled in the delivery of culturally competent care to improve the Indigenous cancer journey and outcomes for Indigenous people. Effective organisational policies and practices are crucial to enable all health professionals to provide culturally competent and responsive cancer care to Indigenous Australians.